Effects of NbC content on microstructural evolution and mechanical properties of laser cladded Fe50Mn30Co10Cr10-xNbC composite coatings. (November 2021) - Li, Xiaofeng; Yang, Xiaohui; Yi, Denghao; Liu, Baosheng; Zhu, Jiacheng; Li, Jiaxing; Gao, Chao; Wang, Linzeng
Abstract: In this paper, NbC reinforced Fe50 Mn30 Co10 Cr10 high entropy alloy coatings with different NbC content were fabricated by laser cladding. The formation mechanism of NbC particles with micro/nano-scale was analyzed. Based on the interaction between the solid-liquid interface and NbC particles, the distribution of micro/nano-scale NbC particles is clarified. The effects of NbC content on microstructure and mechanical properties of the coatings were investigated. It demonstrated that the nanoscale NbC particles restricted the dendritic growth whilst promoting grain nucleation and altering the grain morphology from columnar grain to equiaxed dendrite. Besides, the influence of NbC particles on FCC phase stability was studied based on the lattice mismatch theory, which indicates that the addition of ceramic particles is a new way to modify the phase volume fraction in the dual-phase high-entropy alloys (HEA). The micro-hardness and wear resistance of the coatings significantly improved with the increase of NbC content. For the Fe50 Mn30 Co10 Cr10 -30 wt%NbC high entropy composite coating, the average Vickers hardness and friction coefficient value separately is 525 HV and 0.45. In addition, the large fluctuations on the friction coefficient of the coatings for 10 wt% and 20 wt% NbC addition may be related to the uneven distribution of nanoscale NbC particles in the matrix. Highlights: Fe50 Mn30 Co10 Cr10 -xNbC ( x  = 0, 10, 20 and 30 wt%) composite coatings have been fabricated by laser cladding technique. The formation and distribution mechanism of nano/micronscale NbC particles has been clarified in Fe50 Mn30 Co10 Cr10 -xNbC ( x  = 0, 10, 20 and 30 wt%) HEAs. The effect of nanoscale NbC particles on FCC phase stability has been explained.